1993
DOI: 10.1227/00006123-199302000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Spinal Cord Compression as the Initial Manifestation of Lymphoma

Abstract: Eighteen patients with spinal cord compression caused by previously undiagnosed lymphoma were treated at our institution between 1976 and 1991. There were 14 male and 4 female patients (mean age, 58.2 years). The absence of bony involvement on radiographic images was a feature in 16 of the cases. All patients underwent laminectomy for decompression and tissue diagnosis, after which 5 underwent radiotherapy, 3 underwent chemotherapy, and 10 underwent combined-modality treatment. The functional outcome was impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 26 publications
3
42
1
4
Order By: Relevance
“…3,17 Presentation in the cervical segments is rare because cancer appearing in the paracervical areas is usually discovered early. 2 Similar to data found in the literature, among our patients there were one cervical, eight thoracic and four lumbar lymphoma cases. Magnetic resonance is now indispensable in the diagnosis of the malignant diseases of the spine.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3,17 Presentation in the cervical segments is rare because cancer appearing in the paracervical areas is usually discovered early. 2 Similar to data found in the literature, among our patients there were one cervical, eight thoracic and four lumbar lymphoma cases. Magnetic resonance is now indispensable in the diagnosis of the malignant diseases of the spine.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical intervention is recommended for epidural ML when myelocompression is found. 2,11 The analysis of our current retrospective study of the treatment of epidural ML found data comparable to that in the international literature.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…At a mean observation time of 41.7 months, 5 patients died of their disease, and 7 remained in complete remission. Survival was markedly better than that reported for other malignant extradural tumors (10).…”
Section: Discussioncontrasting
confidence: 61%
“…Neurological findings may include decreased sensory levels, hyperreflexia, paraparesis or paraplegia and bowel or bladder dysfunction (2,9,23). Spinal cord compression has been reported to appear as the first manifestation, but usually back pain tends to precede the onset of myelopathy by a variable period of time (1,18,20). Ramadan (21) reported an incidence of 50% of spinal cord compression in patients with PBL vertebral involvement.…”
Section: Undabeitia J Et Al: Primary Bone Non-hodgkin Lymphoma Of Thmentioning
confidence: 99%